Determinant Factors of Emotional Mental Health in Adolescents: An Exploratory Study - Florensa Florensa; Nurul Hidayah; Lintang Sari; Fajar Yousrihatin; Wulida Litaqia (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Adolescent emotional and mental health is an important component of overall development and well-being. During adolescence, individuals experience significant biological, psychological, and social changes that may increase vulnerability to emotional difficulties. Internal psychological factors such as coping mechanisms, self-esteem, and resilience are considered important determinants influencing adolescent mental health. Objective: This study aimed to explore the determinants of adolescent emotional mental health, particularly emotional difficulties. Research Methodology: This study employed a quantitative descriptive-analytic design. Data were collected from 478 adolescents aged 12–15 years in Pontianak, Indonesia, using structured questionnaires. The variables examined included coping mechanisms, self-esteem, and resilience as independent variables, while emotional difficulties and prosocial strengths served as dependent variables. Data were analyzed using Spearman Rank multivariate analysis to identify the strength and contribution of each determinant factor. Results: Most adolescents had normal prosocial abilities (83.5%), while emotional difficulties were considered normal in 52.7% of respondents. Coping mechanisms had the strongest contribution to emotional difficulties (R² = 0.391; 39.1%), followed by self-esteem (R² = 0.287; 28.7%) and resilience (R² = 0.042; 4.2%). In contrast, prosocial strengths were primarily influenced by resilience (R² = 0.148; 14.8%), followed by coping mechanisms (R² = 0.063; 6.3%) and self-esteem (R² = 0.048; 4.8%). Conclusion: Coping mechanisms, self-esteem, and resilience are significant determinants of adolescent emotional and mental health. Strengthening adaptive coping skills, enhancing self-esteem, and fostering resilience may improve adolescents’ emotional well-being and prosocial development